2009
DOI: 10.1200/jco.2009.27.15_suppl.4537
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of adjuvant capecitabine/cisplatin (XP) versus capecitabine/cisplatin/RT (XPRT) in resected gastric cancer with D2 nodal dissection (ARTIST trial): Safety analysis

Abstract: 4537 Background: Although the adjuvant chemoradiation therapy has gained popularity and has become the standard of care in patients with resected gastric cancer in U.S., the role of chemoradiation therapy after extended D2 dissection has been questioned. We conducted a phase III trial to compare capecitabine/cisplatin (XP) vs XP + radiotherapy (RT) in curatively D2 resected gastric cancer patients in terms of disease free survival and overall survival. Methods: Eligibility criteria were as follows: stage Ib (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Feasibility data of this study were reported at ASCO-GI 2009 showing good toxicity profiles with compliance rates of 75% versus 82% respectively. Survival data of this trial have to be awaited [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility data of this study were reported at ASCO-GI 2009 showing good toxicity profiles with compliance rates of 75% versus 82% respectively. Survival data of this trial have to be awaited [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It further helps to contextualize the benefit of RT seen in INT-0116, and absence of benefit seen in ARTIST. Lastly, the treatment compliance was improved from INT-0116 to ARTIST, with 75% of the XP arm and 82% of the XPRT arm completing the prescribed adjuvant therapy (29,35). Together, ARTIST did not convincingly demonstrate a benefit of adjuvant RT to adjuvant XP-based chemotherapy in an unselected GAC population status post D2 dissection and R0 resection.…”
Section: Postoperativementioning
confidence: 90%
“…Three further large-scale RCTs have attempted to address this question: ARTIST, ARTIST-2, and CRITICS (29)(30)(31)(32)(33)(34). The ARTIST and ARTIST-2 trials, both conducted in South Korea, evaluated the role of adjuvant RT for patients status post D2 dissection and R0 resection, with planned adjuvant chemotherapy in both the control and experimental arms (29,31,33,35). In the ARTIST trial, patients were randomized postoperative to either 6 cycles of adjuvant capecitabine/cisplatin (XP; control arm), or XP with RT (XPRT; experimental arm) (29,35).…”
Section: Postoperativementioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility data of this study were reported at ASCO-GI 2009 showing good toxicity profiles with compliance rates of 75% versus 82%, respectively. Survival data of this trial have to be awaited [Lee et al 2009]. With the low cure rates of the currently accepted therapies, several of the currently accruing Western trials focus on improved chemotherapy schedules: in the British MAGIC-B trial, bevacizumab is added to perioperative epirubicin, cisplatin, and capecitabine.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%